Location and Archaeological Survey of Qoratepa Archaeological Monument (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article highlights the ideas that archaeological sites are important in the study of the period of human society before written history, and that the study of the archeology of Uzbekistan at the present stage is well established.